DETAILS OF THE EVENTS OF THE PERIOD OF SAYID MUHAMMAD KHAN KHANY IN AGAHI’S HISTORICAL WORK “GULSHANI DAVLAT” (TAMADDUN NURI JURNALI, 2025)
The article provides information about the events of the Khiva Khan Sayyid Muhammadkhan and the khanate in the historical work of Muhammad Riza Ogahi “Gulshani Davlat” (The State of the Golden Horde).